The impact of treating parental bipolar disorder and schizophrenia on their children’s mental health and wellbeing: an empty systematic review - Can, Beril; Piskun, Victoria; Dunn, Abby; Cartwright-Hatton, Sam (Frontiers in Psychiatry, 2024)
Background: Parental psychosis (bipolar disorder and schizophrenia) are major risk factors for mental health problems in offspring. Although interventions that focus on parenting and the family environment have shown effectiveness in mitigating this risk, no systematic review has examined the impact of simply treating adult bipolar disorder or schizophrenia on their dependent children's outcomes. Aims: To systematically review the effects (in randomized controlled trials) of adult-based interventions for bipolar disorder and schizophrenia, on offspring mental health and wellbeing. Method: Eligibility criteria included randomized controlled trials that examined the treatment of adults with bipolar disorder and schizophrenia that also included child mental health and wellbeing outcomes. PubMed, Scopus, PsycINFO, and PsychArticles databases were searched. Results: 168,317 studies were reviewed; however, zero studies that met the inclusion criteria could be found. Conclusions: The existing research aimed at treating adult bipolar disorder and schizophrenia has so far overlooked the potential advantages that these treatments could provide for their offspring. This is a missed opportunity to understand the mechanisms of intergenerational transmission. Researchers examining treatments for adults with bipolar disorder and schizophrenia should, where appropriate, consider including both adult and child mental health outcomes in their trials.